Alport syndrome: a genomic to bear in mind - Rivero Rodriguez, Wilmer (2022)
Introduction. Alport syndrome is a heterozygous alteration that affects the alpha chains of type IV collagen, manifesting itself clinically in a variable manner, mainly by persistent hematuria. There are different clinical manifestations in this pathology, fnding cases of chronic renal disease. It is crucial to establish measures that allow timely detection, thus reducing complications. Objective. To describe the relationship and importance between Alport syndrome and renal alterations, highlight the clinical manifestations and therapeutic management. Methods. A literature search was performed in PubMed and Scielo databases oriented towards updated and relevant articles in English or Spanish published in the last 5 years. The relationship betweenAlport syndrome and renal pathology was evaluated to describe clinicalsignifcance, diagnosis and treatment. Results. Different studies show a direct relationship between Alport syndrome and renal dysfunction associated with chronic inflammatory processes. The treatment is not standardized, but is aimed at blocking the renin-angiotensin-aldosterone system. Studies should continue to evaluate the outcome of renal involvement associated with this pathology. Conclusions. Alport syndrome is an important cause of renal dysfunction, especially if it is not associated with treatment; therefore, it is important to make a timely diagnosis through initial suspicion, differential diagnosis and appropriate approach based on the clinical recognition of this entity associated with the deterioration of renal function.